The Value of Urban Flood Modeling - B. R. Rosenzweig; P. Herreros Cantis; Y. Kim; A. Cohn; K. Grove; J. Brock; J. Yesuf; P. Mistry; C. Welty; T. McPhearson; J. Sauer; H. Chang (Earth's Future, 2021)
Abstract Floods are important disturbances to urban socio‐eco‐technical systems and their meteorological drivers are projected to increase through the century due to global climate change. Urban flood models are numerical models that have the capability of representing the features of urban ecosystems and the mechanisms of flooding that impact them. They have the potential to play a critical role in flood risk assessment, operational response, and resilience planning, but existing models remain limited in their capability to represent integrated flooding processes in urban areas and provide the credible quantitative information needed to support risk assessment and resilience practice. Research to advance model development, facilitate intensive watershed monitoring for model parameterization and validation, and support collaboration between researchers and practitioners should be prioritized. This will represent a substantial, expensive effort, but will still be of great value as cities are faced with urgent challenges posed by climate change in coming decades.